Antitumor action of lymphokin-activated сеlls of patients with soft tissue sarcomas and melanomas in dependence on expression of MHC classes I and II antigenes - Berezhnaya, N.M.; Vinnichuk, U.D.; Belova, O.B.; Baranovich, V.V. (Experimental Oncology, 2006)
Aim: To study expression of major histocompatibility complex (MHC) classes І and ІІ antigens and CD25, CD71, Ki-67, CD54, CD56, CD11b, PCNA on lymphocytes and tumor cells and antitumor action of lymphocytes activated with IL-2. Materials and Methods: Tumor explants (soft tissue sarcoma, n = 20, melanoma, n = 25) were co-cultivated in diffusion chambers with autologous lymphocytes; antitumor action was evaluated by morphologic patterns of explant’s growth. Expression of CD25, CD71, Ki-67, CD54, CD56, CD11b, PCNA was evaluated by the method of indirect fluorescence using respective monoclonal antibodies. Results: The highest antitumor action of lymphocytes toward soft tissue sarcoma and melanoma cells is observed if tumor cells are expressing MHC class I antigens. In the cases of soft tissue sarcoma no correlation between the level of antitumor activity of lymphocytes and expression of CD25, CD71, Ki-67, CD54, CD56, CD11b, PCNA has been found, whilst in the case of melanoma it is associated with the high level of CD11b expression. Conclusion: There is a direct correlation between sensitivity of soft tissue sarcoma and melanoma cells to action of lymphokin-activated killer cells and the level of MHC class I antigens.